Ortega’s Philosophy of Technology as a Guide to Action - Diéguez Lucena, Antonio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
The philosophy of technology of Ortega y Gasset has similarities and differences with the subsequently theory formulated by Heidegger. This paper clarifies and evaluates the differences between both. It is argued that Ortega's theses are a guide more appropriate in the current situation to address the risks posed by technological development, and suggests some concrete suggestions for action inspired by them.